(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: The most common dental condition is root canal infection. A focal infection is a localised or widespread infection that is caused by the systemic spread of microbes or their metabolites from one or more different foci of infection. A focus of infection, which is described as "a restricted area that is continuously infected with hazardous bacteria," may exist everywhere in the body. In the literature on medicine and dentistry, the tonsils, adenoids, oral tissues, and other structures have all been considered as potential infection sites. This review will evaluate the current research on the dynamic relationships between infections of endodontic origin, endodontic therapy, and overall health in light of new information that has since come to light. Methods and materials: A comprehensive search was conducted for all non-grey literature published using the online platforms PubMed, MEDLINE, and Scopus, web of sciences. To make sure that all pertinent studies were found, the succeeding search keywords were applied.: “endodontic infections”, “systemic conditions”, “management”, “apical periodontitis”, “diabetes”, “hypertension”. Furthermore, all appropriate scientific papers on role of endodontic infections and their management in different systemic diseases were included. 18 articles were included in the review. Results: Articles showed that the advancement and progression of CVDs have been linked to higher concentrations of inflammatory markers in individuals with periodontitis at root apex, according to a number of systematic reviews and meta-analyses. Persistent periodontitis at root apex may influence the onset and development of atherosclerosis through a number of different possible mechanisms. The literature provides significant support for the notion that people with DM had higher rates of apical periodontitis, larger periapical lesions, and more periapical infections than patients without diabetes. Conclusion: There is growing evidence that prolonged apical periodontitis-related bacteraemia and reduced inflammatory cytokines may have a deleterious impact on systemic health, including CVD development, autoimmune disorders, and diabetic metabolic dysregulation. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.78-88